Clearance of Indocyanine Green in Severe Pediatric Burns - Diaz, Eva Carolina (J Trauma Acute Care Surg, 2019)
BACKGROUND: Clearance of indocyanine green dye (ICGc) reflects sinusoidal perfusion and hepatocyte cell membrane function. Thus, ICGc is a reflection of the functional reserve of intact hepatocytes. The purpose of this study was to identify predictors of ICGc in severely burned children during the acute hospitalization and at the time of discharge from the ICU. A secondary aim was to determine the relationship between liver size and patient ICGc. METHODS: Twenty-six children (0.8 to 17 years old) with 35% or greater total body surface area burned (%TBSA-B) were included. Assessment of ICGc (ml·min(−1)·m(−2)) was done during the acute hospitalization (Median: 6 days after admission, Median: 14 days post-burn) and at the time of discharge from the ICU (Median: 19 days after admission, Median: 27 days post-burn). Age, TBSA-B, % third degree burns, inhalation injury, pre-existing chronic malnutrition, hematocrit, liver dysfunction, and time from burn injury were incorporated in multiple linear regressions as predictive variables of ICGc. Only variables with p<0.05 were retained in the final models. RESULTS: Time from injury and age were the strongest predictors of ICGc during the acute admission but not at the time of discharge from the ICU. Time from injury was negatively associated with ICGc, whereas age was positively associated. At the time of discharge from the ICU, ICGc was increased in proportion to the %TBSA-B, whereas inhalation injury and pre-existing chronic malnutrition were associated with lower ICGc. There was no correlation between change-to-predicted liver length and ICGc. CONCLUSIONS: The intrinsic ability of the liver to extract ICG from plasma was lower in younger burned patients during the acute admission, and in those with pre-existing chronic malnutrition and inhalation injury at the time of discharge from the ICU.